2018
DOI: 10.1021/acs.jmedchem.8b01361
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art in Respiratory Syncytial Virus Drug Discovery and Development

Abstract: Respiratory syncytial virus (RSV) is a globally prevalent viral infection with limited treatment options which hospitalizes millions each year. Treatment options have been limited to palivizumab, a monoclonal antibody, approved for prophylaxis in high-risk infants and ribavirin with very limited efficacy and significant safety concerns. This Perspective surveys the range of direct acting antiviral agents (DAAs) that target key steps in the viral life cycle. A number of approaches to DAAs have produced landmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 97 publications
(209 reference statements)
0
59
0
Order By: Relevance
“…Nucleoside analogs that terminate RNA chain synthesis have been identified (Clarke et al, 2015;Deval et al, 2015;Wang et al, 2015), and one such compound, ALS-8176, has shown efficacy in RSV-infected adults (DeVincenzo et al, 2015). Several non-nucleoside small-molecule inhibitors have also been identified (Cockerill et al, 2019;Fearns and Deval, 2016), and although some (for example, BI-compound D) are known to disrupt RNA cap addition (Liuzzi et al, 2005), there are additional inhibitor classes for which the mechanism of action is not well understood (Duvall et al, 2016;McCutcheon et al, 2015). P serves as an essential polymerase cofactor that tethers L to the nucleoprotein-RNA complex (García et al, 1993;Grosfeld et al, 1995;Yu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoside analogs that terminate RNA chain synthesis have been identified (Clarke et al, 2015;Deval et al, 2015;Wang et al, 2015), and one such compound, ALS-8176, has shown efficacy in RSV-infected adults (DeVincenzo et al, 2015). Several non-nucleoside small-molecule inhibitors have also been identified (Cockerill et al, 2019;Fearns and Deval, 2016), and although some (for example, BI-compound D) are known to disrupt RNA cap addition (Liuzzi et al, 2005), there are additional inhibitor classes for which the mechanism of action is not well understood (Duvall et al, 2016;McCutcheon et al, 2015). P serves as an essential polymerase cofactor that tethers L to the nucleoprotein-RNA complex (García et al, 1993;Grosfeld et al, 1995;Yu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these predictions, we decided to stabilize the transient -helix of P (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Given that at least 16 to 18 residues are usually required to successfully stabilize an -helix in aqueous solution (22), and that Phe28 appeared to fit well into the helical wheel representation, we decided to focus on P (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). A stapled peptide scan of P (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)…”
Section: Resultsmentioning
confidence: 99%
“…Given that at least 16 to 18 residues are usually required to successfully stabilize an -helix in aqueous solution (22), and that Phe28 appeared to fit well into the helical wheel representation, we decided to focus on P (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). A stapled peptide scan of P (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) was performed by inserting the all-hydrocarbon cross-link at the hydrophilic face of the helix, the presumed non interacting face of the helix. (19).…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic monoclonal antibodies (mAbs) have become a prospective part of infectious diseases due to their specificity, limited off-target effects, and favourable safety profile. Primary examples of mAbs as treatment are palivizumab against respiratory syncytial virus and ZMapp against Ebola virus [17,18].…”
Section: Introductionmentioning
confidence: 99%